PERANAN TENAGA PENGAJAR (DOSEN) PROFESIONAL DALAM PEMBENTUKAN KARAKTER MAHASISWA UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DI PROGRAM STUDI PENDIDIKAN LUAR SEKOLAH - Wau, Yasaratodo; Anifah, Anifah; Zati, Vidya Amalia (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
ABSTRACT The purpose of research here is To be able to describe the role of professional teaching staff (Lecturer) in the formation of student characters. To be able to describe the role of professional faculty (Lecturer) in improving the quality of learning, to see the role of professional teaching staff (Lecturer) and the formation of student character in improving the quality of learning in the Out of School education program. The type of this research is quantitative descriptive research. This research is a research using regression analysis research two predictor. Data analysis technique used in this research In this study used the data validity and data reliability test method in viewing the role of professional lecturers in the formation of student character to improve the quality of learning through the initial test and final test. Data analysis technique in the form of quantitative descriptive method then used frequency table with product moment correlation formula.For result of this research is There is existence of reabel data from 15 items to 30 respondents with result 80,1% between role of lecturers (lecturer) professional in forming student character for improvement of learning quality. To see hypothesis test from X1 data with Y then used correlation test and regression 2 person variable. The result of X1 data to Y has a significant role between professional teaching staff with learning quality with correlation data X1 = 5,75% to data Y = 0,01%. Correlation data X2 to Y has significant and valid data between variables X2 and Y. The data has a role of 7.35% formation of student characters on the quality of learning 0.1%. The data of linear regression analysis 2 predictors between X1, X2 and Y. The data result is 0.737% with 0.543%. Where has a significant and valid role between professional faculty in the formation of student characters to improve the quality of learning diprodi outside education faculty of science faculty of state universities university. Kata Kunci: Guru Profesional, Pembangunan Karakter, Kualitas Pembelajaran